2021
DOI: 10.1371/journal.pone.0258922
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between obesity-related anthropometric indicators and cognitive function in Chinese suburb-dwelling older adults

Abstract: Background Studies relating obesity to cognition in older people show conflicting results, which may be explained by the choice of obesity indicators. Objectives This study aimed to investigate the relationship between obesity-related indicators and cognitive impairment, especially between different age or gender subgroups, and explore whether obesity-related indicators were related to specific cognitive domains. Methods This was a cross-sectional study on 1753 participants aged ≥ 60 years (41.0% men; aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The authors’ previous studies have shown that both sarcopenia ( Chen et al, 2021 ) and obesity ( Ma et al, 2021 ) are associated with cognitive impairment. Therefore, this study explores the gender differences in the prevalence of MCI and the correlation between multiple influencing factors.…”
Section: Introductionmentioning
confidence: 99%
“…The authors’ previous studies have shown that both sarcopenia ( Chen et al, 2021 ) and obesity ( Ma et al, 2021 ) are associated with cognitive impairment. Therefore, this study explores the gender differences in the prevalence of MCI and the correlation between multiple influencing factors.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairment was defined as a score of ≤17 for illiterates, ≤20 for participants with primary school education and ≤24 for those with junior high school degrees or above. 12 Balance ability was determined by the result of the chair rising test (CRT), the timed up and go test (TUG) and the tandem gait test (TGT). Poor balance ability was defined as CRT >10 s or TUG >12 s or TGT <8 steps.…”
Section: Methodsmentioning
confidence: 99%
“…Obesity is a chronic illness that can lead to an increased risk of lower quality of life and premature death [ 1 ]. Body fat, besides representing a major risk factor for different chronic diseases such as type II diabetes mellitus, fatty liver disease, hypertension, myocardial infarction, stroke, osteoarthritis, kidney disease, dyslipidemias, obstructive sleep apnea and cancer [ 2 , 3 ], may also represent a significant predictor of impaired cognitive performance, accelerated cognitive decline, and dementia [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In this vein, many studies have explored the possible link binding executive functions to body weight.…”
Section: Introductionmentioning
confidence: 99%